2022
DOI: 10.1038/s41598-022-18638-2
|View full text |Cite
|
Sign up to set email alerts
|

Human preferences toward algorithmic advice in a word association task

Abstract: Algorithms provide recommendations to human decision makers across a variety of task domains. For many problems, humans will rely on algorithmic advice to make their choices and at times will even show complacency. In other cases, humans are mistrustful of algorithmic advice, or will hold algorithms to higher standards of performance. Given the increasing use of algorithms to support creative work such as text generation and brainstorming, it is important to understand how humans will respond to algorithms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Correct advice was followed in approximately half of their decisions and incorrect advice in about a tenth. Other studies have found similar effects 17 , 19 , indicating that people often follow advice regardless of whether it is correct or not 9 , 10 , 16 . Participants’ tendency towards overreliance may be attributed to the advice serving as a decision anchor.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Correct advice was followed in approximately half of their decisions and incorrect advice in about a tenth. Other studies have found similar effects 17 , 19 , indicating that people often follow advice regardless of whether it is correct or not 9 , 10 , 16 . Participants’ tendency towards overreliance may be attributed to the advice serving as a decision anchor.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, it has also been shown that individuals are more willing to adhere to algorithmic than human advice ( algorithmic appreciation 15 ). This tendency is particularly evident in tasks with measurable outcomes that require logical problem-solving or in judgments under uncertainty 16 . The underlying mechanisms leading to either algorithmic aversion or appreciation are not yet fully understood, with several advice characteristics proposed as potentially relevant, including the quality of advice.…”
Section: Introductionmentioning
confidence: 99%
“…AI inconsistencies in underserved patient populations are a known issue 22 . Automation bias 23 , 24 is another related pitfall that roots in the overreliance of the radiologists in a computerized system. Regardless of this potential risk, the trial’s main conclusions remain unaltered, by design, as the endpoint is objectively measured on the final reports, directly.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they found evidence for "algorithmic appreciation," where individuals preferred algorithmic advice over human advice, including their own judgments, when compared directly. The inclination to favor algorithms was observed in several "objective" areas, such as logic problems (Dijkstra et al, 1998), word association task (Bogert et al, 2022), assessing the magnitude of visual stimuli (Logg et al, 2019), predicting product demand (Daschner & Obermaier, 2022), and choosing lottery numbers (Farjam, 2019). It was also evident in taste-related contexts, such as ranking the popularity of songs, predicting romantic attraction (Logg et al, 2019), and divulging personal information and feelings (Lucas et al, 2014).…”
Section: Algorithms As Decision Aiding Toolsmentioning
confidence: 99%